Structural Model Analysis of Electric Vehicle Usage Decisions as an Implementation of Sustainable Development Goals (SDGs) in Society 5.0 - Lesmana, Jajat (Ebiz Prima Nusa, 2025)
Aims the increasingly pressing issue of climate change, electric vehicles have emerged as one of the promising solutions to reduce greenhouse gas emissions and achieve the Sustainable Development Goals (SDGs). In the context of sustainable development, the transition to more environmentally friendly transportation is becoming increasingly important. Behind its popularity, there are complex factors that influence consumer decisions in choosing and using electric vehicles. The most fundamental question is on what basis do consumers prefer electric vehicles. Data collection was carried out using purposive sampling of 233 respondents. The respondent criteria were male or female who were stated to be at least 17 years old, either having an electric vehicle or not having an electric vehicle. Data were collected using a questionnaire with a Likert scale of 1-7. Data were analyzed using SmartPLS 3 software to model structural equations between variables. The results showed that the decision to use electric vehicles (Y) was directly influenced by Green Marketing (X1), Quality (X2) and Brand Image (Z1) by 66.7%. At the structural level, the Decision to Use Electric Vehicles (Y) is most significantly influenced (p-value 0.001 < 0.05) by Green Purchase Intention (Z1) and Brand Image (Z2) with a path coefficient of 0.117.